Сравнительный анализ методов сужения подмножества Парето-оптимальных вариантов речевых кодеков - Скорик, Ю. В. (ХНУРЕ, 2010)
In given article a number of the formalized methods of a choice of a unique variant of system from some set of variants of systems taking into account set of indicators of quality on the basis of the additional subjective information received from experts is analyzed.
Keywords: Методы сужения Парето-оптимальных решений; речевой кодек